Single Nucleotide Polymorphism Assay for Genetic Identification of Lophophora williamsii*. Issue 6 (29th July 2020) - Lee, Minji; Jung, Ju Yeon; Choi, Sungsoo; Seol, Ilung; Moon, Seohyun; Hwang, In Kwan
Abstract: Lophophora is a member of the Cactaceae family, which contains two species: Lophophora williamsii and L. diffusa . Lophophora williamsii is an illegal plant containing mescaline, a hallucinogenic alkaloid. In this study, a novel method based on a single nucleotide polymorphism (SNP) assay was developed for identifying L. williamsii ; this assay reliably detects SNPs within chloroplast DNA ( rbcL, matK, and trnL‐trnF IGS) and was validated for identifying Lophophora and L. williamsii simultaneously. The chloroplast DNA sequences from four L. williamsii and three L. diffusa plants were obtained and compared using DNA sequence data from approximately 300 other Cactaceae species available in GenBank. From this sequence data, a total of seven SNPs were determined to be suitable for identifying L. williamsii . A multiplex assay was constructed using the ABI PRISM ® SNaPshot™ Multiplex Kit (Applied Biosystems, Forster City, CA) to analyze species‐specific SNPs. Using this multiplex assay, we clearly distinguished the Lophophora among 19 species in the Cactaceae family. Additionally, L. williamsii was distinguished from L. diffusa . These results suggest that the newly developed assay may help resolve crimes related to illegal distribution and use. This multiplex assay will be useful for the genetic identification of L. williamsii and can complement conventional methods of detecting mescaline.